Entrepreneurship development program: Branding and marketing innovation during the pandemic - Dian Arief Pradana; Herdiana Dyah Susanti; Rifka Arinda Noviasari; Winda Hurotul ‘Aini; Moh. Fahrurrozi; Elok Rosyidah; M. Iswahyudi (Community Empowerment, 2021)
The Covid-19 pandemic has resulted in many businesses experiencing a slump. The decline occurred because businesses were not ready to adapt to changing consumer preferences. Shops and supermarkets, which are usually crowded with consumers, are now suddenly deserted because consumers prefer to stay at home. Business owners must innovate, especially in terms of marketing to maintain their existence during the pandemic. This activity aims to improve the entrepreneurial skills of students and alumni to survive during the pandemic. The method of implementing this entrepreneurship development program is carried out in the form of a webinar with the theme Branding and Marketing Innovation During the Covid-19 Pandemic. The total number of participants is approximately 80 students and alumni. The results of the activity showed that the webinar activity really helped the participant's business to be able to grow and survive the pandemic. It is hoped that this webinar can increase creativity and bring up participant innovation to become strong entrepreneurs in the midst of the COVID-19 pandemic.